Impact of predicted climate change environmental conditions on the growth of Fusarium asiaticum strains and mycotoxins production on a wheat-based matrix - Cervini, Carla; Naz, Naoreen; Verheecke-Vaessen, Carol; Medina, Angel (Elsevier, 2024)
Fusarium asiaticum is a predominant fungal pathogen causing Fusarium Head Blight (FHB) in wheat and barley in China and is associated with approximately £201 million in annual losses due to grains contaminated with mycotoxins. F. asiaticum produces deoxynivalenol and zearalenone whose maximum limits in cereals and cereals-derived products have been established in different countries including the EU. Few studies are available on the ecophysiological behaviour of this fungal pathogen, but nothing is known about the impact of projected climate change scenarios on its growth and mycotoxin production. Therefore, this study aimed to examine the interacting effect of i) current and increased temperature (25 vs 30 °C), ii) drought stress variation (0.98 vs 0.95 water activity; aw) and iii) existing and predicted CO2 concentrations (400 vs 1000 ppm) on fungal growth and mycotoxin production (type B trichothecenes and zearalenone) by three F. asiaticum strains (CH024b, 82, 0982) on a wheat-based matrix after 10 days of incubation. The results showed that, when exposed to increased CO2 concentration (1000 ppm) there was a significant reduction of fungal growth compared to current concentration (400 ppm) both at 25 and 30 °C, especially at 0.95 aw. The multi-mycotoxin analysis performed by LC-MS/MS qTRAP showed a significant increase of deoxynivalenol and 15-acetyldeoxynivalenol production when the CH024b strain was exposed to elevated CO2 compared to current CO2 levels. Zearalenone production by the strain 0982 was significantly stimulated by mild water stress (0.95 aw) and increased CO2 concentration (1000 ppm) regardless of the temperature. Such results highlight that intraspecies variability exist among F. asiaticum strains with some mycotoxins likely to exceed current EU legislative limits under prospected climate change conditions.
Keywords: Fusarium graminearum species complex; Water stress; Carbon dioxide; Trichothecenes; Zearalenone